Surgical Options for Resectable Lung Adenosquamous Carcinoma: A Propensity Score-Matched Analysis - Zhu, Shuncang; Ge, Tao; Xiong, Yicheng; Zhang, Jing; Zhu, Di; Sun, Liangdong; Song, Nan; Zhang, Peng (Frontiers in Oncology, 2022)
Background Surgery is the primary treatment option for Lung adenosquamous carcinoma (ASC) patients. However, no study compares the benefits of lobectomy and sublobar resection in ASC patients. Methods A total of 1379 patients in the Surveillance, epidemiology, and End Results (SEER) database and 466 patients in Shanghai Pulmonary Hospital (SPH) were enrolled. Survival benefits were evaluated after possible confounders were eliminated by propensity score matching (PSM). Results After 1:3 PSM, 463 SEER database patients and 244 SPH patients were enrolled. Lobectomy was associated with better overall survival (OS) and disease-free survival (DFS) than sublobar resection for ASC patients (5-year OS of SEER: 46.9% vs. 33.3%, P =0.017; 5-year OS of SPH: 35.0% vs. 16.4%, P =0.002; 5-year DFS of SPH: 29.5% vs. 14.8%, P =0.002). Similar results were observed in stage I patients. Univariate and multivariate Cox regression analyses showed that sublobar resection was an adverse prognostic factor independently (SEER: HR: 1.40, 95%CI: 1.08-1.81, P =0.012; SPH: HR: 1.73, 95%CI: 1.11-2.70, P =0.015). Subgroup analysis showed that all of the ASC patient subtypes tended to benefit more from lobectomy than sublobar resection. Conclusions Lobectomy remains the primary option for ASC patients compared to sublobar resection, including stage I.